A Corpus review on literacy reading materials 2019 - LestariningsihDewi Nastiti; Mutiara; SumarsihNanik; KristantoDody; DuantikaPrima; Herlinda; M.Yusuf; Mutiya; DhaneswaraWedya (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Language structure and context, which are suitable for the target reader, are very necessary to make a good children’s storybook. In his regard, a tool is required to detect word consistency and to support structure and context-building. A tool to detect this requirement is the vocabulary children’s book corpus. This study aims at determining a suitable book level for target children. This has an impact on children’s storybook users who see the story as an appropriate parameter on their reading level. In this research, the corpus used refers to how the texts are treated in the annotated corpus. By analyzing sentences and classifying words through the corpus, authors and users of children’s books can see the word lists that have a high-medium-low frequency. The data were gained from literacy reading materials in Badan Pengembangan and Pembinaan Bahasa in 2019. The information was gathered using antcon-derived document analysis. The vocabulary levels for each child and early graders can be seen in the appearance frequencies of the vocabulary for both levels. Based on the 13 data points included in the top order, nouns for elementary school are no longer found and the use of quotation marks for early readers has been introduced.